Are Children from Divorced Single-Parent Families Disadvantaged? New Evidence from the China Family Panel Studies. Issue 1 (1st January 2020) - Zhang, Chunni
Abstract: Since the beginning of the twenty-first century, divorced single parenthood has become more prevalent in China. Nevertheless, divorced single parenthood and its impact on child outcomes have not been studied as much in China as in the West. Most studies in Western societies have reported that divorce and single parenthood are associated with disadvantaged child outcomes. This has been attributed in part to the prevalence of divorce among parents with low socioeconomic status and decreased child monitoring when one parent is absent. In China, however, there are several buffering mechanisms that may reduce the negative impact of divorce on children. Using data from four waves of the China Family Panel Studies, this study examines the effects of divorce and single parenthood on children's academic performance and subjective wellbeing. The results show that children living with divorced single mothers performed as well as children from intact families, whereas children living with divorced single fathers and stepparents were disadvantaged in academic performance and subjective wellbeing. Frequent quarrels between parents in intact families also had a negative impact on child outcomes.